Perceptions of the Role of West Virginia’s Cooperative Extension Service in Tobacco Control Coalitions - Reed, Donald; Lester, Dana; Danberry, Kathy; Fink, Peggy Lambert; Owens, Sherry (Frontiers in Public Health, 2016)
Despite the fact that the consequences of tobacco use are well identified and known, it remains the single most preventable cause of disease and death in the United States. In West Virginia alone, the adult prevalence of cigarette smoking is 26.8%. This study researches the perceptions of the Cooperative Extension Service’s involvement and role in county-level coalitions that address tobacco use in West Virginia. The research findings provide practical areas to increase the role of the Extension Service in these vital efforts to save lives, reduce economic hardships on families, and reduce the health-care burden on the state government.